Discriminating Contagion : An Alternative Explanation of Contagious Currency Crises in Emerging Markets - Ahluwalia, Pavan (IMF Working Papers; Working Paper ;, 2000)
This paper shows that a country's vulnerability to contagious crises depends on the visible similarities between that country and other countries that are experiencing crises. A country is vulnerable to shifts in investor sentiment if it exhibits weaknesses in the same economic variables as other countries affected by a contagious crisis (particularly the country that started the contagious wave), or if it is located in the same region. The paper uses a sample of 19 emerging markets, and data from the Mexican, Asian, and Russian crises to provide evidence of this discriminating contagion, after controlling for alternative channels of contagion such as trade spillovers and financial linkages.